2017
DOI: 10.1002/adsc.201700694
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Synthesis of Dibenzo[1,5]diazocines from β‐(2‐Aminophenyl)‐α,β‐ynones

Abstract: beta-(2-Aminophenyl)-alpha,beta-ynones afforded exclusively challenging dibenzo[1,5]diazocines by means of (JonPhosAuNCMe)SbF6 catalysis. In contrast with the known gold-catalyzed reaction path of 2-alkynylanilines that leads to indoles, ynones underwent an auto intermolecular hydroamination. This process resulted finally in the formation of an eight-membered ring, likely through a selective 8-exo-dig intramolecular hydroamination that prevailed over the possible cyclocondensation reaction (that would result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…More recently, β‐(2‐aminophenyl)‐α,β‐ynones afforded 3‐unsubstituted 2‐acylindoles in good yields in the presence of 20 mol% AgOTf under (microwave) MW heating . Furthermore, the same substrates resulted starting reagents for the preparation of a wide range of useful dibenzodiazocines through a gold‐catalyzed tandem auto intermolecular hydroamination followed by a regioselective 8‐exo‐dig ‐cycloamination …”
Section: Methodsmentioning
confidence: 99%
“…More recently, β‐(2‐aminophenyl)‐α,β‐ynones afforded 3‐unsubstituted 2‐acylindoles in good yields in the presence of 20 mol% AgOTf under (microwave) MW heating . Furthermore, the same substrates resulted starting reagents for the preparation of a wide range of useful dibenzodiazocines through a gold‐catalyzed tandem auto intermolecular hydroamination followed by a regioselective 8‐exo‐dig ‐cycloamination …”
Section: Methodsmentioning
confidence: 99%
“…It has been found that β‐(2‐aminophenyl)‐α,β‐ynones 181 under catalysis with (JonPhosAuNCMe)SbF 6 are selectively dimerized to form dibenzo[1,5]diazocines 182 (Scheme 57). [159] The reaction starts with an intermolecular hydroamination, which is followed by an intramolecular hydroamination.…”
Section: Synthesis Of Polycyclic Systemsmentioning
confidence: 99%
“…When dimerization of β‐(2‐aminophenyl)‐α,β‐ynones 57 is catalyzed by (JonPhosAuNCMe)SbF 6 , a series of dibenzo[1,5]diazocine 208 is formed through 8 ‐exo‐dig intramolecular hydroamination process (Scheme 64). [130] …”
Section: ‐Alkynylanilines In the Synthesis Of Seven‐ And Eight‐member...mentioning
confidence: 99%